1991
DOI: 10.1111/j.1365-2265.1991.tb00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous aminobisphosphonate in Paget's disease: clinical, biochemical, histomorphometric and radiological responses

Abstract: Intravenous 3-amino-1-hydroxypropylidene-1, 1-bisphosphonic acid (APD) was used to treat 26 patients with Paget's disease. Three daily dosages were studied; 20-30 mg/day in 20 patients, 45 mg/day in three patients and 60 mg/day in three patients, by daily 4-hour infusions for 2-10 days. The fasting urinary hydroxyproline excretion (HypE) declined exponentially, reaching 50% of pretreatment values at 1.92 +/- 0.16 (mean +/- SEM) days. This initial rapid decline was complete by 4 days following treatment to a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 27 publications
2
15
1
4
Order By: Relevance
“…A high frequency of arthralgia and myalgia after the first IV infusion of pamidronate, even in those who received only 10 mg, highlights the potential difficulties in ensuring effective patient blinding during the conduct of a placebo‐controlled trial with this agent. The observed frequency was higher than that reported in previous studies evaluating pamidronate in metabolic bone disease (26), and our results therefore could at least partly reflect some degree of expectation bias. On the other hand, the similar high frequency of adverse events in the 2 treatment arms does suggest that the strategy of using a 10‐mg dose of pamidronate as the comparator arm as opposed to placebo was successful in ensuring effective patient blinding.…”
Section: Discussioncontrasting
confidence: 83%
“…A high frequency of arthralgia and myalgia after the first IV infusion of pamidronate, even in those who received only 10 mg, highlights the potential difficulties in ensuring effective patient blinding during the conduct of a placebo‐controlled trial with this agent. The observed frequency was higher than that reported in previous studies evaluating pamidronate in metabolic bone disease (26), and our results therefore could at least partly reflect some degree of expectation bias. On the other hand, the similar high frequency of adverse events in the 2 treatment arms does suggest that the strategy of using a 10‐mg dose of pamidronate as the comparator arm as opposed to placebo was successful in ensuring effective patient blinding.…”
Section: Discussioncontrasting
confidence: 83%
“…The mode of bisphosphonates action is still not completely clear but it has been shown that pamidronate suppresses the accession of osteoclast precursors onto bone, and their transformation into mature osteoclasts [2,3]. Pamidronate is generally well tolerated [5][6][7][8][9], but some patients treated for the first time develop a transient, selflimiting, febrile reaction alone or associated with flu-like symptoms (e.g., malaise and myalgias) and hematological changes [2, 5-7, 9, 10]. This reaction closely resemble the acute phase response (APR) found only with bisphosphonates that, like pamidronate, contain nitrogen.…”
mentioning
confidence: 98%
“…Etidronate, pamidronate and clodronate are clinically useful in diseases with increased bone resorption, particularly Paget's disease and hypercalcemia of malignancy [7][8][9]41,42]. Risedronate, etidronate, and clodronate affect experimental bone model systems to different degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The main biological effect is a decrement in bone resorption through inhibition of osteoclast activity. The bisphosphonates have been used to treat a variety of disorders characterized by increased bone resorption, including Paget's disease, hypercalcemia, metastatic bone disease, and recently osteoporosis [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Presently, only etidronate and alendronate are approved for osteoporosis treatment.…”
Section: Introductionmentioning
confidence: 99%